AN ANALYSIS ABOUT HATE SPEECH TOWARDS PRESIDENT JOKO WIDODO ON HIS INSTAGRAM ACCOUNT: A PRAGMATICS ANALYSIS. - Famelia Ranti Repelita Simbolon; Devi Melisa Saragi (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2019)
The purposes of this qualitative research are: (1) to find out the meanings and aims of hate speech on Joko Widodo's Instagram account. (2) to find out the functions of the illocutionary act of hate speech on Joko Widodo's Instagram account. (3) to find out the dominant function of hate speech on Joko Widodo's Instagram account. The data of this research are the comments of netizens found on Joko Widodo's Instagram account. The first result of this study shows that all the comments found on Jokowi's Instagram aim at indignation, defamation, blasphemy, distastefulness, provocation, incitement, and forgery. The second result is that the functions of illocutionary acts on Jokowi's Instagram account consist of 30 directives, 137 representatives, 7 commissives, 65 expressive, and no declaration. The third one is that the dominant function found on Jokowi's Instagram is representatives attaining 55,70% classified into 36 comments as giving an opinion, 33 comments as telling or reporting, 25 comments as complaining, 22 comments as stating, and 21 comments as suggesting.